Pheno and genotyping of Staphylococcus aureus, isolated from bovine milk samples from São Paulo State, Brazil - Cabral, K. G.; Lämmler, C.; Zschöck, M.; Langoni, Hélio [UNESP]; De Sá, M. E. P.; Victória, Cassiano [UNESP]; Silva, A. V. da (Canadian Science Publishing, 2004)
In the present study, 87 Staphylococcus aureus isolates obtained from milk samples of 87 cows with mastitis in 6 different municipal districts of 2 regions of São Paulo State, Brazil, were compared pheno and genotypically. Pulsed-field gel electrophoresis (PFGE) analysis of the strains was performed, and PCR was carried out to detect genes for a number of staphylococcal cell surface proteins, exoproteins, and 3 classes of agr genes. Nine distinct S. aureus lineages (LA-LI) were identified by PFGE. The lineages LA and LE, which accounted together for 63 strains (72.2%), were prevalent and had been collected from all of the 6 municipal districts, indicating a broad geographic distribution of these lineages; LB, LC, LD, LF, LG, LH, and LI, however, were isolated sporadically and accounted for 24 strains (27.8%). Some characteristics, like penicillin resistance and the presence of cap8 and agr class II genes, were associated with the prevalent lineages (LA and LE), and penicillin susceptibility and the presence of cna and cap5 genes were associated with sporadic lineages. According to the present results, some S. aureus lineages possess a combination of genes that confer the propensity to cause and disseminate infection, and only a limited number of clones are responsible for the cases of bovine mastitis on the various farms. © 2004 NRC Canada.
Keywords: Genotyping; Mastitis; Phenotyping; S. aureus; Cloning; Drug products; Electrophoresis; Genes; Proteins; Infections; Pulsed-field gel electrophoresis (PFGE); Staphylococcus aureus; Bacteria; antibiotic agent; cell surface protein; DNA; erythromycin; gentamicin; minocycline; oxacillin; penicillin G; protein; tetracycline; microbiology; antibiotic sensitivity; bacterial gene; bacterium isolation; Brazil; cell lineage; gene amplification; genotype; geographic distribution; mastitis; milk; nonhuman; penicillin resistance; phenotype; polymerase chain reaction; priority journal; pulsed field gel electrophoresis; Animals; Bacterial Proteins; Bacterial Typing Techniques; Cattle; Dairying; DNA, Bacterial; Electrophoresis, Gel, Pulsed-Field; Female; Genotype; Mastitis, Bovine; Microbial Sensitivity Tests; Milk; Phenotype; Restriction Mapping; Staphylococcal Infections; Bovinae